2016
DOI: 10.1111/1750-3841.13542
|View full text |Cite
|
Sign up to set email alerts
|

Ohmic Heating of an Electrically Conductive Food Package

Abstract: Ohmic heating through an electrically conductive food package is a new approach to heat the food and its package as a whole after packing to avoid post-process contamination and to serve consumer needs for convenience. This process has been successfully completed using polymer film integrated with an electrically conductive film to form a conductive package. Orange juice packed in the conductive package surrounded with a conductive medium was pasteurized in an ohmic heater. A mathematical model was developed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The proximate analysis indicated that the sausages were composed of 55.67% moisture content, 15.53% protein, 25.75% lipid, 3.55% carbohydrate, and 2.08% ash. The density of sausages decreased with temperature increase, as shown in Table 1 , whereas that of the PP package was 900 kg/m 3 , obtained from the study of Kanogchaipramot et al [ 17 ].…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…The proximate analysis indicated that the sausages were composed of 55.67% moisture content, 15.53% protein, 25.75% lipid, 3.55% carbohydrate, and 2.08% ash. The density of sausages decreased with temperature increase, as shown in Table 1 , whereas that of the PP package was 900 kg/m 3 , obtained from the study of Kanogchaipramot et al [ 17 ].…”
Section: Resultsmentioning
confidence: 96%
“…The electrical conductivity of the sausages, with varying temperatures, is depicted in Table 1 . The electrical conductivity of PP was 0.0011 S/m, according to the study of Kanogchaipramot et al [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations